Paediatric cataract surgery with 27G vitrectomy instrumentation: the Ghent University Hospital Experience - Chan, Hwei Wuen; Van den Broeck, Filip; Cools, Axelle; Walraedt, Sophie; Joniau, Inge; Verdin, Hannah; Balikova, Irina; Van Nuffel, Stefaan; Delbeke, Patricia; De Baere, Elfride; Leroy, Bart P.; Nerinckx, Fanny (Frontiers in Medicine, 2023)
Objective: To describe a cohort of paediatric patients who underwent unilateral or bilateral lens extractions at Ghent University hospital using the Dutch Ophthalmic Research Center (D.O.R.C.) ultra-short 27G vitrectomy system Methods: Retrospective analysis of the medical and surgical records of all children that underwent lens extraction between September 2016 and September 2020 using the D.O.R.C. ultra-short 27G vitrectomy system Results: Seventy-two eyes of 52 patients were included. The most important aetiologies in this study were of secondary (25.5%), developmental (13.7%), or genetic (13.7%) nature. No definitive cause could be established in more than a quarter of cases (27.5%) despite extensive work-up, deeming them idiopathic. The remainder of cases (19.6%) was not assigned a final aetiologic designation at the time of the study due to contradicting or missing diagnostic data. This study couldn’t identify any cataract cases related to infection or trauma. Surgical complications rate was 61.1% of which posterior capsule opacification was the most frequent with a rate of 25%. A significant short-term postoperative best-corrected visual acuity gain (≤ -0.2 LogMAR) was observed in 60.5% of eyes for which usable acuity data were available (n=38). Conclusions: Many different instruments and techniques have been described and used in the context of paediatric lens extractions, each with its advantages and disadvantages. This study illustrates that an ultra-short 27G vitrectomy system can be used to perform paediatric lens extractions with good surgical outcomes. Further studies and comparative trials are needed to ascertain this further.